Pendidikan Keimanan dalam al-Qur`an - Fauzana Annova (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2019)
This paper discusses the education of faith in the Qur'an, this research is a philosophical normative study, and philosophical, substantial. The method used is descriptive analytic supported by authoritative sources. This study concludes that the implementation of faith education has several stages that must be passed, so that the cultivation of understanding of faith in students becomes easier. The first stage involves planting the root of the faith, namely monotheism (tauhid). After the creed of tauhid is firmly planted, after that it is continued with the cultivation of other pillars of faith. Faith education is declared successful if a person has the characteristics of a believer, namely khusyu’ in prayer, abstaining from useless deeds, purifying the soul with zakat, guarding genitals, keeping mandates and promises and always carrying out prayer rituals.